2010
DOI: 10.1038/nature09515
|View full text |Cite
|
Sign up to set email alerts
|

Distant metastasis occurs late during the genetic evolution of pancreatic cancer

Abstract: SummaryMetastasis, the dissemination and growth of neoplastic cells in an organ distinct from that in which they originated 12, is the most common cause of death in cancer patients. This is particularly true for pancreatic cancers, where most patients are diagnosed with metastatic disease and few show a sustained response to chemo- or radiation therapy 3. Whether the dismal prognosis of patients with pancreatic cancer compared to patients with other types of cancer is a result of late diagnosis or early dissem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

78
1,748
6
24

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 2,209 publications
(1,895 citation statements)
references
References 20 publications
78
1,748
6
24
Order By: Relevance
“…These observations should support a genetic progression model of pancreatic carcinogenesis leading to invasive cancer 5, 6, 7, 8, 9, 10. Recently, the estimated lifetime of clonal evolution during PC development and progression based on a computational model using many autopsy cases has been reported 11, 12. This model suggested an average of 11.7 years from the initiating carcinogenesis until development of the parental clone, an average of 6.8 years to the development of metastatic subclones within the primary PC, and an average of 2.7 years until death of the case (Figure 1).…”
Section: Opportunity To Diagnose ‘Early Pancreatic Cancer’mentioning
confidence: 62%
“…These observations should support a genetic progression model of pancreatic carcinogenesis leading to invasive cancer 5, 6, 7, 8, 9, 10. Recently, the estimated lifetime of clonal evolution during PC development and progression based on a computational model using many autopsy cases has been reported 11, 12. This model suggested an average of 11.7 years from the initiating carcinogenesis until development of the parental clone, an average of 6.8 years to the development of metastatic subclones within the primary PC, and an average of 2.7 years until death of the case (Figure 1).…”
Section: Opportunity To Diagnose ‘Early Pancreatic Cancer’mentioning
confidence: 62%
“…In addition, the imbalances of SNP allele frequencies were used to correctly predict an LOH on chromosome 3 in only a subset of the tumour samples. Recent studies found genomic heterogeneity in breast cancer 10,24 , pancreatic cancer 25,26 , and B-cell chronic lymphocytic leukemia 9 , as well as mosaic amplifications of tyrosine kinase receptor genes in glioblastoma 27 . Together, these findings provide compelling evidence for clonal evolution as a general mechanism in cancer development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to inter‐tumoral (or patient specific) variation, significant intra‐tumoral variation is evident in many tumor types, in forms spanning histological to genetic heterogeneity. Such variability may be reflective of regional foci of clonal evolution (Yachida et al., 2010), as well as tumor self‐seeding from disseminated cancer cells (Comen et al., 2011). Moreover, the heterogeneity of putative tumor‐initiating cells (or cancer stem cells) may contribute to subtype variation in certain solid tumor types, as suggested by studies employing mouse models of glioblastoma, intestinal, and prostate cancer (Visvader, 2011).…”
Section: Addressing Tumor Heterogeneity and Complexitymentioning
confidence: 99%
“…This figure is suspected to be an underestimation of the mutational landscape of individual tumors, as the analytic techniques that have been used most frequently, such as PCR‐based sequencing of DNA extracted from total tumor lysates, may not detect mutations occurring in subclonal tumor cell populations (Loeb, 2011; Sellers, 2011). This is illustrated, for example, by exomic sequencing of separate, histologically distinct regions micro‐dissected from individual human pancreatic ductal carcinomas (PDACs): each showed a specific mutational repertoire indicative of multiple subclonal populations within the same primary tumor (Yachida et al., 2010). Consistent with these findings, recent whole‐genome deep (or high‐throughput) sequencing analysis of individual tumors has revealed that a particular tumor specimen may contain up to 50,000 different non‐synonymous mutations affecting several hundred genes, with mutation rates of 0.5–20 per megabase (Loeb, 2011; Sellers, 2011).…”
Section: Addressing Tumor Heterogeneity and Complexitymentioning
confidence: 99%